2017
DOI: 10.1039/c7ra05687g
|View full text |Cite
|
Sign up to set email alerts
|

Propionic acid-based deep eutectic solvents: synthesis and ultra-deep oxidative desulfurization activity

Abstract: Propionic acid-based deep eutectic solvents (C3H6O2/X ZnCl2, X from 0.1 to 0.6) were synthesized by stirring a mixture of propionic acid and zinc chloride at 100 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Mao and co-workers investigated the ability of propionic acid-based DESs with different compositions of ZnCl 2 as HBD to convert DBT into DBT sulfone in the presence of H 2 O 2 . 120 Interestingly, the conversion of DBT increased with the change of the C 3 H 6 O 2 -to-ZnCl 2 molar ratio from 1 : 0.1 to 1 : 0.5, but decreased drastically when the molar ratio reached 1 : 0.6 (Fig. 9c).…”
Section: Application Of Deep Eutectic Solvents (Dess) In Odsmentioning
confidence: 89%
“…Mao and co-workers investigated the ability of propionic acid-based DESs with different compositions of ZnCl 2 as HBD to convert DBT into DBT sulfone in the presence of H 2 O 2 . 120 Interestingly, the conversion of DBT increased with the change of the C 3 H 6 O 2 -to-ZnCl 2 molar ratio from 1 : 0.1 to 1 : 0.5, but decreased drastically when the molar ratio reached 1 : 0.6 (Fig. 9c).…”
Section: Application Of Deep Eutectic Solvents (Dess) In Odsmentioning
confidence: 89%
“…As a new type of green solvents, research on DESs has intensified in the last decade, ever since their potential in new chemical technologies was realized [29,30]. Among the existing literatures, the ODS of fuels using DESs has attracted wide attention [31][32][33][34][35][36][37][38]. Li's group synthesized a series of acidic DESs for deep oxidation/extraction desulfurization of model fuels and the desulfurization efficiency of such DESs reached up to 99.99% [31].…”
Section: Introductionmentioning
confidence: 99%
“…Li's group utilized the DES choline chloride/2 polyethylene glycol for desulfurization and the removal of DBT reached up to 99.1% [33]. Mao et al [34] reported a class of propionic acid-based DESs (C3H6O2/X ZnCl2, X = 0.1-0.6) and the desulfurization of DBT reached 99.42%. In a previous work, we found that the aromaticity of sulfur compounds was weakened by strong hydrogen bonding interactions in DESs, leading to easier oxidation to the corresponding sulfones by peracids [35].…”
Section: Introductionmentioning
confidence: 99%
“…In previous oxidative desulfurization systems, the dosage of DESs was very high, e.g., the DES and model diesel volume ratio was 0.5:1 (1:2) in the ChCl/ p ‐TsOH system and 0.15:1 (about 1:6.7) in propionic acid‐based DESs . Therefore, the acetamide‐based DESs demonstrate excellent performance as only a small amount of DES is used.…”
Section: Resultsmentioning
confidence: 87%